Be fruitful and multiply? Anglican efforts to control fertility in interwar England - Moeller, A (2022)
This thesis examines the moral justification offered by Anglican leaders for their support for eugenic, pronatalist, and neo-Malthusian schemes between the First and Second World Wars. It argues that Anglican leaders comprehended their widespread efforts to control fertility within the context of a broader struggle over competing conceptions of human purpose in English society, and that these women and men regularly justified their efforts on the grounds that fertility-manipulation schemes served to align procreative behaviours with ‘Christian’ conceptions of human purpose. Additionally, this thesis argues that key aspects of the shared moral logic of Anglican leaders can help to explain the pervasive interest in birthrate patterns, along with the enduring appeal of fertility-manipulation schemes, amongst middle- and upper-class men and women of varying religious and political persuasions in England, as well as across Europe and North America, during the first half of the twentieth century. Furthermore, it sheds light on how population concerns led to the liberalization of Church of England teachings on marriage, sexuality, and procreation, and also provides a qualitative contribution to the historiography on secularization by illuminating how Anglican leaders sought to maintain moral influence in the face of perceived large-scale rejection of Christian moral teachings.